TRANSFORMATION OF CRIMINAL LAW IN ADDRESSING CYBERCRIME IN E- COMMERCE TRANSACTIONS WITHIN THE JURISDICTION OF RIAU REGIONAL POLICE - Haikal Ananda Assyabab; Heni Susanti (Proceeding International Conference on Social Sciences, 2026)
The rapid development of digital technology has significantly transformed the economic, social, and legal structures of modern society. The growth of e-commerce has shifted transaction patterns from conventional to fully digital ecosystems. This shift has led to new, complex, and transnational cybercrimes. This research aims to analyze the transformation of criminal law in addressing cybercrime in e-commerce transactions and to evaluate law enforcement mechanisms within the jurisdiction of Riau Regional Police. Using a juridical- empirical method, this study combines normative legal analysis of Law No. 11 of 2008 concerning Electronic Information and Transactions (ITE Law) with field data collected in 2025. The findings reveal that law enforcement officers face constraints, including limited human resources, lack of digital forensic expertise, and weak institutional coordination. A comprehensive reform of criminal law and strengthened digital governance are urgently needed to establish an adaptive and just criminal justice system.